INVESTIGATION: LEARNING TAHFIDZ QUR'AN FOR STUDENTS WITH SPECIAL NEEDS IN ISLAMIC-BASED SCHOOLS - Muchamad Irvan; Ahsan Romadlon Junaidi; Atifah Nur Zahidah; Nurul Fitra Febriana; Siti Mutmainah (Proceedings Series of Educational Studies, 2023)
Discussions regarding the ability of children with special needs to follow tahfidz of the Qur'an often arise, "Can children with special needs memorise the Qur'an? How is the planning carried out so that children can memorise the Qur'an? How are modifications to the memorisation method applied?" This research aims to find answers to a phenomenon that occurs in Islamic-based schools which produce memorisers of the Qur'an from students with special needs. Qualitative methods were applied at all stages of this research. Data collection was carried out using interview, observation and documentation techniques, and then validity was carried out by testing the validity of the data using triangulation and member check techniques. The research results found that there was planning, implementation of memorisation using the talaqqi method, evaluation and involvement of parents in learning the tahfidz Qur'an for students with special needs.